Escalofrios, Como consegui mi cabeza humana reducida - Stine, R. L. (Nueva York : Scholastic, 2003)
Mark's Aunt Benna presents him with a gift of a shrunken head from the jungle island of Baladora, and it is giving him a strange, dangerous power.
Translation of: How I got my shrunken head.
"Scholastic en espanol"--Cover.
4.0.
008-012.
Text in Spanish.
Keywords: Shrunken heads -- Juvenile fiction; Head -- Juvenile fiction; Spanish language materials -- Juvenile fiction; Horror fiction; Fiction